2006
DOI: 10.1007/s10661-005-9037-0
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the relationships betweenmacroinvertebrate community composition and physical andchemical habitat characteristics in farm dams

Abstract: Recently, Australian interest in farm dams has focused on rates of harvest of surface waters (runoff), and the impact this has on nearby natural systems. Little research has been directed towards the role of these artificial water bodies in sustaining biological reserves within the wider ecosystem. Macroinvertebrate communities in three farm dams in the Central Tablelands of New South Wales were surveyed, and water quality variables were correlated with species richness and abundance. Community responses to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The physical and chemical conditions in a given habitat will support a characteristic set of richness and diversity levels of macroinvertebrate species (Heino 2000;Brainwood and Burgin 2006). In the salinas studied, macroinvertebrate diversity differentiates the evaporating ponds from the others and can be considered as a good indicator of these saline environments.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and chemical conditions in a given habitat will support a characteristic set of richness and diversity levels of macroinvertebrate species (Heino 2000;Brainwood and Burgin 2006). In the salinas studied, macroinvertebrate diversity differentiates the evaporating ponds from the others and can be considered as a good indicator of these saline environments.…”
Section: Discussionmentioning
confidence: 99%
“…Brainwood and Burgin (2006) found that water quality and physical habitat were most strongly implicated in defining the suite of species present in the dams. Of the physical habitat parameters, sediment depth and canopy cover were most strongly linked with the observed macroinvertebrate communities.…”
Section: Discussionmentioning
confidence: 99%
“…As reported for farm ponds overseas, Australian farm dams can provide a variety of sustainable reservoirs of biodiversity in the landscape. The Raglan dams were found to have diverse macroinvertebrate assemblages with considerable variation among habitats within dams, and seasonally (Brainwood and Burgin 2006). These different assemblages were influenced by water quality, which was linked to land use and groundwater quality, with the water sources and relative impact of each varying among the three dams (Brainwood et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations